Regional meeting on the pilot plan of the bachelor degree - Autores, Varios (2000)
On December 4, 1999, in the city of Sicuani, province of Canchis, the "Regional meeting on the high school pilot plan" was held, in compliance with the commitment to action assumed by the Board of Education in the Social Week of the South Andean , which consists of giving critical follow-up to the pilot experience of the high school. According to the schedule, this meeting had the character of a workshop, in which group work was carried out with cards prepared for the parents, teachers, students, and institutions that participated in the meeting.